N-Heterocyclic Carbene (NHC)–Copper(I) Complexes as Catalysts for A3 Reactions - Chen, Ming-Tsz; Navarro, Oscar (Synlett, 2013)
The use of easily synthesized NHC–Cu(I) complexes for the preparation of a variety of propargylamines through an A3 coupling scheme is described.
Keywords: N-heterocyclic carbine; copper; homogeneous catalysis; multicomponent reaction; green chemistry